Analisa Batuan Alterasi Panas Bumi Arjuno-Welirang Berdasarkan Sifat Mineraloginya - Bakruddin Bakruddin; Widya Utama (LPPM Politeknik Aceh Selatan, 2017)
This research has been conducted on the geothermal area of Arjuno-Welirang, the with aim to know the alteration of rocks based on their mineralogical properties. The method used is X-ray Diffraction by using Shimadzu X-ray Diffraction technique, Co-Kɒ radiation (ɒ = 1.54060 Å). Mineral phase obtained from Padusan rock samples are 9 minerals ie Aragonite and followed by other minor phases. Then on Cangar rock samples, there are 7 mineral phases with core minerals, ie Silicon Oxide and followed by phase of other minerals.